Case Report: A Neuro-Ophthalmological Assessment of Vision Loss in a Pediatric Case of McCune-Albright Syndrome - Lemme, Jordan D.; Tucker-Bartley, Anthony; Drubach, Laura A.; Shah, Nehal; Romo, Laura; Cay, Mariesa; Voss, Stephan; Kwatra, Neha; Kaban, Leonard B.; Hassan, Adam S.; Boyce, Alison M.; Upadhyay, Jaymin (Frontiers in Medicine, 2022)
Patients diagnosed with McCune-Albright Syndrome (MAS) frequently manifest craniofacial fibrous dysplasia (FD). Craniofacial FD can impinge nerve fibers causing visual loss as well as craniofacial pain. Surgical decompression of affected nerves is performed, with variable efficacy, in an attempt to restore function or alleviate symptoms. Here, we present a case of a 12-year-old MAS patient with visual deficits, particularly in the left eye (confirmed by enlarged blind spots on Goldmann visual field testing), and craniofacial pain. Decompression surgery of the left optic nerve mildly improved vision, while persistent visual deficits were noted at a 3-month follow-up assessment. An in-depth, imaging-based evaluation of the visual system, including the retinal nerve fiber layer, optic nerves, and central nervous system (CNS) visual pathways, revealed multiple abnormalities throughout the visual processing stream. In the current FD/MAS patient, a loss of white matter fiber density within the left optic radiation and functional changes involving the left primary visual cortex were observed. Aberrant structural and functional abnormalities embedded within central visual pathways may play a role in facilitating deficits in vision in FD/MAS and contribute to the variable outcome following peripheral nerve decompression surgery.